DOI: 10.11606/d.59.2015.tde-16072015-164909
|View full text |Cite
|
Sign up to set email alerts
|

Variação espacial e temporal de microcrustáceos planctônicos do lago Monte Alegre e experimentos abordando a influência da qualidade do alimento sobre o desempenho dos cladóceros

Abstract: analisar a influência da quantidade e qualidade do alimento sobre os parâmetros de tabela de vida de duas espécies de cladóceros encontradas no lago, utilizando o séston de cada zona. Fatores físicos e químicos do séston também foram avaliados no período dos experimentos. D. birgei mostrou preferência pela zona litorânea e D. ambigua pela zona limnética, enquanto C. richardi e D. gessneri não apresentaram preferência significativa.A qualidade do alimento não influenciou de maneira negativa o desenvolvimento de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…A new structuring of species dominance, with a preponderance of copepods and a medium-sized r-strategist cladoceran (C. richardi), which is competitively superior to a larger species (D. gessneri) (Ferreira, 2013), was apparent in the last two periods. The success or recovery of some populations after the key period may be related to the ability to occupy also the littoral zone of the lake, where Chaoborus and mites are less abundant, as observed for B. tubicen (Arcifa et al, 2013;Souza, 2015). We presume that these areas are not permanent habitats, but serve to maintain a minimum population density and enable the reoccupation of the limnetic zone when conditions are more favourable, as we are observing for B. tubicen.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…A new structuring of species dominance, with a preponderance of copepods and a medium-sized r-strategist cladoceran (C. richardi), which is competitively superior to a larger species (D. gessneri) (Ferreira, 2013), was apparent in the last two periods. The success or recovery of some populations after the key period may be related to the ability to occupy also the littoral zone of the lake, where Chaoborus and mites are less abundant, as observed for B. tubicen (Arcifa et al, 2013;Souza, 2015). We presume that these areas are not permanent habitats, but serve to maintain a minimum population density and enable the reoccupation of the limnetic zone when conditions are more favourable, as we are observing for B. tubicen.…”
Section: Discussionmentioning
confidence: 62%
“…Bosmina can respond to changes in predation pressure by invertebrate predators with increasing size and change of some carapace structures, as reported in a review of paleolimnological studies (Korosi et al, 2013). In Lake Monte Alegre in 2011-12, the size of B. tubicen and D. ambigua was significantly larger in the warm season compared to the cool one, when Chaoborus larvae were more abundant (Souza, 2015). Carter et al (2008) observed a smaller body size of D. ambigua exposed to kairomones from a mite species, indicating that the response to predators can vary according to their type and selectivity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Rubenstein (1984) showed that the gerrid Gerris remigis Say remains in microhabitats with better food quality and, consequently, better reproductive capacity. In macrophyte stands of the lake, a wide variety of microhabitats can be found, that contribute to a greater diversity of invertebrates (Meschiatti and Arcifa, 2002;Cleto-Filho and Arcifa, 2006), including planktonic cladocerans and copepods (Souza, 2015). Terrestrial invertebrates are also abundant in macrophytes, such as insects that eventually fall on the water, becoming vulnerable to predation (Domingos, 2012 -personal observation).…”
Section: Discussionmentioning
confidence: 99%